Clone Detection in Matlab Stateflow Models - Dean, Thomas; Chen, Jian; Alalfi, Manar (Electronic Communications of the EASST, 2014)
Matlab Simulink is one of the leading tools for model based software development in the automotive industry. One extension to Simulink is Stateflow, which allows the user to embed Statecharts as components in a Simulink Model. These state machines contain nested states, an action language that describes events, guards, conditions and actions and complex transitions. As Stateflow has become increasingly important in Simulink models for the automotive sector, we extend previous work on clone detection of Simulink models to Stateflow components.